2019
DOI: 10.26677/tr1010.2019.132
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Trade Openness, Economic Growth, Exchange Rate and Tariff Rate: Evidence from Northeast Asia

Abstract: The article aims to investigate the relationship between trade openness, economic growth, exchange rate and tariff rate in three Northeast Asian countries between 1998 and 2017 using a vector autoregressive model. We found that GDP growth rate has a positive relationship with trade openness. Tariff rate positively affects both GDP growth rate and exchange rate. However, trade openness has a negative effect on exchange rate. We also found that there is a directional relationship running from trade openness to G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…In the case of Economic Community of West African States (ECOWAS) countries, a significant and positive relationship between trade openness and economic growth was observed [52]. Another remarkable study by Nguyen [53] conducted in three Northeast Asian countries found that trade openness accelerates the level of economic growth. Additionally, trade openness has a unidirectional relationship with economic growth and a bidirectional causal relation with the exchange rate.…”
Section: Introductionmentioning
confidence: 97%
“…In the case of Economic Community of West African States (ECOWAS) countries, a significant and positive relationship between trade openness and economic growth was observed [52]. Another remarkable study by Nguyen [53] conducted in three Northeast Asian countries found that trade openness accelerates the level of economic growth. Additionally, trade openness has a unidirectional relationship with economic growth and a bidirectional causal relation with the exchange rate.…”
Section: Introductionmentioning
confidence: 97%